Identification of the Glyceraldehyde-3-Phosphate Dehydrogenase (GeGAPDH) Gene Family in Gastrodia elata Revealing Its Response Characteristics to Low-Temperature and Pathogen Stress - Yaxing Yan; Mei Jiang; Pengjie Han; Xiaohu Lin; Xiao Wang (Plants)
The glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene plays a pivotal role in the glycolysis/gluconeogenesis process, contributing significantly to glycosyl donor synthesis, plant growth and development, and stress responses. Gastrodia elata Bl., a heterotrophic plant in the Orchidaceae family, has its dried tubers used as the traditional Chinese medicine. This study identified three GeGAPDH genes in G. elata, all encoding basic, stable, hydrophilic proteins. Phylogenetic analysis and subcellular localization predictions categorized GeGAPDH1 as a plastid subtype, while GeGAPDH2 and GeGAPDH3 were classified as cytoplasmic subtypes. Prokaryotic expression experiments demonstrated successful expression of the GeGAPDH1 protein in Escherichia coli, which exhibited significant GAPDH enzymatic activity. Subcellular localization experiments showed that GeGAPDH1 was localized in the plastid. Expression analysis indicated that the three GeGAPDH genes were predominantly expressed in tubers. Under low-temperature stress, although the total GAPDH enzyme activity in tubers did not change significantly, the expression of GeGAPDH1 was significantly up-regulated, while GeGAPDH2 and GeGAPDH3 were significantly down-regulated. This suggests that different subtypes of GeGAPDH may regulate cold resistance through different pathways. Upon pathogen infection, the GeGAPDH gene family exhibited pathogen-specific regulatory patterns. During infection by Fusarium oxysporum, both the expression levels of all three GeGAPDH genes and the total GAPDH enzyme activity in tubers increased significantly; however, F. solani infection induced a significant increase in total GAPDH enzyme activity without significant changes in gene expression. These results suggest that the GeGAPDH gene family may respond to different pathogen infections through transcriptional or translational regulation mechanisms. This study systematically identified and characterized the GeGAPDH gene family in G. elata, providing a theoretical foundation for understanding the functional differentiation of GAPDH in heterotrophic plants.